Sistem Kendali Navigasi Ar Drone Berbasis Pengenalan Teks Dengan Menggunakan Metode Optical Character Recognition - Haqqi Rizqi; Gembong Edhi Setyawan; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Quadcopter is one of Unmanned Aerial Vehicle which is used such a field of defense, agriculture and other fields. UAVs have proven their usefulness like the Amazon E-commerce giant that uses UAV as a medium of delivery of orders to customers with guaranteed goods will arrive in approximately half an hour. Many features of developed Quadcopter UAVs such as face recognition, object tracking and landing on specific objects. Along with the benefits that are increasingly widespread in various areas of features owned needs to be upgraded again like a feature to perform automatic navigation by simply reading the text on an image. So in this study has designed a navigation system on the type of Ar Drone quadcopter using optical character recognition based on the graphical programming using LabVIEW. The result show accuracy of reading text found the best distance is 1 m with 100% success.